Effect of Team Development Intervention on Disaster Volunteer’s Problem-Solving Ability and Team Work Process - Perwira, Luqman Tifa; Hidayat, Muhammad (Universitas Ahmad Dahlan, 2023)
This study investigates the impact of team development training interventions on teamwork effectiveness, as manifested by the team's problem-solving ability and the quality of their collaborative efforts. The experimental research design employed in this study involved two independent groups (a between-group design) with a singular dependent variable. The experimental group comprised 10 participants who underwent team development training interventions, while the control group, also consisting of 10 participants, underwent a placebo treatment in the form of psychological first-aid training. The assessment methodology utilized a group problem-solving test, specifically employing simulation games involving scenarios such as traffic jam and bomb squad simulations. The measurement outcomes revealed a substantial difference (44%) in task completion duration between the control and experimental groups. During the task completion, the Mann-Whitney test yielded a Z-value of -2.612, with an Asymp. Sig. (two-tailed) value of 0.009 (<0.01), indicating a significant difference in the assessment scores for the task completion process between the control and experimental groups. The interventions provided are proven to improve team cognition and affect, stimulating constructive team behavior in completing the task the groups face